Isolation and characterization of fetal nucleated red blood cells from maternal blood as a target for single cell sequencing‐based non‐invasive genetic testing. (14th June 2021) - Ito, Noriko; Tsukamoto, Kazuhiro; Taniguchi, Kosuke; Takahashi, Ken; Okamoto, Aikou; Aoki, Hiroaki; Otera‐Takahashi, Yuka; Kitagawa, Michihiro; Ogata‐Kawata, Hiroko; Morita, Hideaki; Hata, Kenichiro; Nakabayashi, Kazuhiko
Abstract: Purpose: Although non‐invasive prenatal testing (NIPT) based on cell‐free DNA (cfDNA) in maternal plasma has been prevailing worldwide, low levels of fetal DNA fraction may lead to false‐negative results. Since fetal cells in maternal blood provide a pure source of fetal genomic DNA, we aimed to establish a workflow to isolate and sequence fetal nucleated red blood cells (fNRBCs) individually as a target for NIPT. Methods: Using male‐bearing pregnancy cases, we isolated fNRBCs individually from maternal blood by FACS, and obtained their genomic sequence data through PCR screening with a Y‐chromosome marker and whole‐genome amplification (WGA)‐based whole‐genome sequencing. Results: The PCR and WGA efficiencies of fNRBC candidates were consistently lower than those of control cells. Sequencing data analyses revealed that although the majority of the fNRBC candidates were confirmed to be of fetal origin, many of the WGA‐based genomic libraries from fNRBCs were considered to have been amplified from a portion of genomic DNA. Conclusions: We established a workflow to isolate and sequence fNRBCs individually. However, our results demonstrated that, to make cell‐based NIPT targeting fNRBCs feasible, cell isolation procedures need to be further refined such that the nuclei of fNRBCs are kept intact.